2003
DOI: 10.1029/2002jd002381
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability and timing of growing‐season CO2 exchange in a boreal forest

Abstract: [1] We studied the interannual variability of cumulative net ecosystem CO 2 exchange (NEE) and its connection with cumulative or average climatic variables during five growing seasons. The analysis was based on a 5-year-long time series of CO 2 flux measured from April 1996 to April 2001 in a Scots pine forest in southern Finland by the eddy covariance technique. The onset of the ecosystem growing season was best connected with air temperature, and the end of the growing season was best connected with day leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 27 publications
7
83
4
Order By: Relevance
“…Our estimate for the mean NEP in the 1990s (0.10 kg/m 2 /year) is in the midrange of NEP measurements taken at six forest sites in the Nordic countries, varying from a carbon source equal to 0.09 kg/m 2 /year to a carbon sink equal to 0.25 kg/m 2 /year [73]. On the other hand, our estimate is lower than measurements taken at a 40-year-old Scots pine stand in southern Finland, where they ranged from 0.23 to 0.31 kg/m 2 /year between 1997 and 2000 [63]. The measurements were high for this site probably because the tree stand was still young and growing vigorously in the most productive part of the country.…”
Section: Reliability Of the Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…Our estimate for the mean NEP in the 1990s (0.10 kg/m 2 /year) is in the midrange of NEP measurements taken at six forest sites in the Nordic countries, varying from a carbon source equal to 0.09 kg/m 2 /year to a carbon sink equal to 0.25 kg/m 2 /year [73]. On the other hand, our estimate is lower than measurements taken at a 40-year-old Scots pine stand in southern Finland, where they ranged from 0.23 to 0.31 kg/m 2 /year between 1997 and 2000 [63]. The measurements were high for this site probably because the tree stand was still young and growing vigorously in the most productive part of the country.…”
Section: Reliability Of the Resultscontrasting
confidence: 49%
“…Such inter annual variability is important on a site scale based on measurements of carbon fluxes [63] and on a global scale based on ecosystem modelling [40], inverse modelling [2] or satellite observations [53]. This variability has not, however, been accounted for in earlier regional scale studies based on field inventories because it has not been possible to derive the annual estimates from these inventories [9].…”
Section: Annual Variability In Forest Carbon Balancementioning
confidence: 99%
“…This finding is in line with the study by Lohila et al (2007) where they found that an afforested boreal peatland turned from a net sink to a source of carbon during rainy days in the summer. Total NEE at the Kalevansuo drained peatland forest from spring to early summer (25 April-21 June, −102 g C m −2 ) is comparable to NEE values reported from boreal forests growing on mineral or peat soils (Suni et al, 2003;Lohila et al, 2007).…”
Section: Co 2 Fluxessupporting
confidence: 61%
“…The main source of this variability was attributed to the growing season length (GSL). In a boreal Scots pine forest, Suni et al (2003) also reported a low interannual variability in NEE, which was mainly related to the temperature. In a coniferous -deciduous mixed forest, Carrara et al (2003; attributed the large internannual variability to both GSL and to the annual temperature.…”
Section: Neementioning
confidence: 99%